Blind Confidence in Automation - Pope Pius XII (Relations industrielles / Industrial Relations, 1956)
This is the basic theme of a letter addressed to the president and participants of the 43rd French Social Week in Marseilles. It was sent on behalf of Pope Pius XII by Msgr. Angelo Dell'Acqua, Vatican Substitute Secretary of State for Ordinary Affairs.

Social Documents: Credit - Pope Pius XII (Relations industrielles / Industrial Relations, 1952)
The following text is an English translation by the National Catholic Welfare Conference of the discourse given in the French language by His Holiness Pope Pius XII on October 24, 1951, to delegates from 46 nations attending the International Congress on Credit Questions. In his discourse, the Pontiff discussed the moral and social importance of credit and encouraged its fruitful extension.

Occupational Corporative Order - Pope Pius XII (Relations industrielles / Industrial Relations, 1952)
The following text is an English translation by the National Catholic Welfare Conference of the address pronounced in January 31th 1952 by His Holiness Pope Pius XII to the Italian Catholic Association of Employers in which he asked for the Christian spirit as the basis for the social order and criticized forced co-determination.